Development of Indicators for Teachers’ Positive Attitudes Towards Educational Supervision - Tepsiri, Siridet; Sudrung, Jurairat (Journal of Research Methodology, 2023)
This research was aimed to (1) develop the indicators of teachers’ positive attitudes towards educational supervision and (2) validate the consistency of the model of the positive-attitude indicators for educational supervision and empirical data. The population consisted of secondary school teachers from Bangkok's Office of Educational Service Areas 1 and 2. The sample of 486 teachers was drawn using a multi-stage random sampling process. Content synthesis was employed to create construct elements. The experts evaluated the instrument's content validity by confirming the consistency between the question and the definition of the indicators. Coverage of questions using the IOC (Index of Item-Objective Congruence) index. The research instruments consisted of (1) Formative assessment of components and indicators for positive attitudes towards educational supervision (2) Questionnaire of positive attitudes toward educational supervision. Descriptive statistics: frequency, percentage, mean, standard deviation, coefficient of variation, skewness, and kurtosis were used to analyze the data. In addition, the relationship between the indicators was analyzed by using Pearson's product-moment coefficient with SPSS for Windows version 21. Second-order confirmatory factor analysis was also used with the model and the empirical data via LISREL Program version 8.0. The result of this research showed that the teachers’ positive attitudes towards educational supervision consisted of 3 components 16 indicators; (1) Cognitive component 1.1) Has the correct knowledge of supervision 1.2) Understanding of supervision. 1.3) Convinced that supervision is the professional development of teachers. (2) Affective component 2.1) Seeing the importance and benefits of supervision 2.2) Willing to receive supervision 2.3) Accept and trust the supervisor. (3) Behavioral component 3.1) Readily accepted and listens to outcomes and suggestions for supervision. 3.2) Co-operate effectively with Supervisors. 3.3) Use the results of supervision to develop teaching and learning management. 3.4) Enthusiasm for self-development. 3.5) Having good relations with supervisors. 3.6) Participate in school supervision. 3.7) Helping fellow teachers by using the supervision process. 3.8) Motivate other teachers to be positive towards supervision. 3.9) Support and encourage co-educators to participate in supervision or supervised activities. 3.10) Publicize activities for supervision in the school. And to examine the coherence of the positive attitude towards teacher supervision model with the empirical data. using a second corroborative component analysis. It was found that the positive attitude towards teacher supervision model was consistent with the empirical data (χ2(59, N = 486) = 74.26, p = .09, GFI = .98, AGFI = .96, RMR < .01, RMSEA = .02).